An ELM based multi-agent system and its applications to power generation - Yaw C.T.; Wong S.Y.; Yap K.S.; Yap H.J.; Amirulddin U.A.U.; Tan S.C. (IOS Press, 2023)
Benchmarking; Electric circuit breakers; Knowledge acquisition; Learning systems; Neural networks; Pattern recognition; Power generation; Activation functions; Benchmark datasets; Certified belief in strength; Circulating water system; Extreme learning machine; ITS applications; Trust management; Trust measurement; Multi agent systems